Psoriasis: Obesity and Fatty Acids - Kunz, Manfred; Simon, Jan C.; Saalbach, Anja (Frontiers in Immunology, 2019)
Psoriasis is chronic inflammatory skin disease of high prevalence affecting skin, joints, cardiovascular system, brain, and metabolism. The pathogenesis of psoriasis is mediated by a complex interplay between the immune system, inflammatory mediators of different pathways, e.g., TNF-alpha and the IL-23/IL-17 pathways, psoriasis-associated susceptibility loci, autoantigens, and multiple environmental factors. The disease has a significant genetic background as shown by a strong association with well-defined MHC markers and specific single-nucleotide variants in inflammatory mediators. Environmental factors such obesity and nutrition have an important impact on onset and severity of psoriasis. Epidemiologic studies define a bidirectional link between psoriasis and obesity with obesity predisposing to psoriasis and psoriasis favoring obesity. The pathogenic links between genetics, chronic inflammation and metabolic state in psoriasis are currently investigated in more detail. The present minireview aims at a more comprehensive understanding of the risk factors for psoriasis with focus on immunogenetics and obesity.